2020
DOI: 10.1002/2211-5463.12803
|View full text |Cite
|
Sign up to set email alerts
|

Potential prognostic impact of EBV RNA‐seq reads in gastric cancer: a reanalysis of The Cancer Genome Atlas cohort

Abstract: Epstein–Barr virus (EBV)‐associated gastric cancer (EBVaGC), whose prognosis remains controversial, is diagnosed by in situ hybridization of EBV‐derived EBER1/2 small RNAs. In The Cancer Genome Atlas (TCGA) Stomach Adenocarcinoma (STAD) project, the EBV molecular subtype was determined through a combination of multiple next‐generation sequencing methods, but not by the gold standard in situ hybridization method. This leaves unanswered questions regarding the discordance of EBV positivity detected by different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A closely followed study by the ACRG found 6.5% of EPV-positive GC patients [ 8 , 185 ]. An even higher positivity rate has been reported, when EBV was detected by RNA-Seq instead of traditional EBER1/2 in situ hybridization [ 186 ].…”
Section: Ebv and Gastric Carcinogenesismentioning
confidence: 99%
“…A closely followed study by the ACRG found 6.5% of EPV-positive GC patients [ 8 , 185 ]. An even higher positivity rate has been reported, when EBV was detected by RNA-Seq instead of traditional EBER1/2 in situ hybridization [ 186 ].…”
Section: Ebv and Gastric Carcinogenesismentioning
confidence: 99%
“…In contrast, EBV infection‐related EAC has not been described. Immunohistochemical analysis reveals that EBV‐associated gastric carcinomas contain more tumor infiltrating lymphocytes than actual tumor cells, constituting on average 50% of CD8 + T cells and 20% CD68 + macrophages, and express programmed death‐ligand 1 in 70% of EBV‐associated gastric carcinomas 90,91 …”
Section: Epidemiological Featuresmentioning
confidence: 99%
“…In addition, HBV and HCV sequences have been reported in a subset of liver carcinomas, and EBV gene expression has been elucidated in a subset of gastric carcinomas. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 Oncogenic viruses cause tumors by producing transforming proteins or non-coding RNAs (ncRNAs) that affect cell biology by acting on critical cellular targets. 24 At least one oncogene is encoded by each known human tumorigenic viruses.…”
Section: Introductionmentioning
confidence: 99%